Advancements in Sensitivity Testing for Hepatitis C Screening: A Literature Review of Innovations, Challenges, and Clinical Effectiveness - Abdullah Alanazi,; Erlina Abdullah, (International Journal of Medical Toxicology and Legal Medicine, 2024)
Early detection of HCV is crucial for initiating timely treatment and reducing transmission, particularly in high-risk populations. This review explores advancements in sensitivity testing for Hepatitis C virus (HCV), focusing on innovations, challenges, and clinical effectiveness. Nucleic Acid Testing (NAT) has significantly enhanced diagnostic capabilities by detecting HCV RNA much earlier than antibody-based tests, reducing the window period and improving patient outcomes. However, the high cost and technical complexity of NAT limit its widespread adoption, particularly in low and middle-income countries (LMICs). Rapid Diagnostic Tests (RDTs) offer a more accessible and cost-effective alternative in resource-limited settings, although they generally have lower sensitivity, especially in early-stage infections. Recent innovations in RDT technology, including dual-detection mechanisms for both antibodies and antigens, have improved their clinical utility but cannot fully replace NAT in accuracy. This review also addresses the variability in test performance across different populations influenced by factors such as age, immune status, and co-infection with other viruses like Human Immunodeficiency Virus (HIV). These factors create challenges in standardizing screening programs globally, as tests that perform well in one population may not be effective in another. The need for tailored diagnostic approaches that account for these variables is critical for ensuring accurate and early detection of HCV in diverse regions. While technological advancements have improved HCV diagnostics, challenges related to cost, accessibility, and test variability persist. Continuous innovation and investment in affordable and accessible diagnostic tools are necessary to expand global screening efforts, particularly in LMICs. Addressing these challenges is essential for achieving the World Health Organization’s goal of eliminating HCV as a public health threat by 2030.